Crossing borders: trends in Operations and Global Supply Chain Management - Corrêa, Henrique (Brazilian Journal of Operations & Production Management, 2013)
The management of global supply chains and the impact of 3BL do not represent a rupture but rather another stage of evolution in the expansion of scope that the area of operations management has been experiencing since the beginning of the 20th Century. It is a fact, however, that the current stage of evolution is occurring in a more accelerated rate than in previous stages and it is also a fact that the levels of volatility, complexity and social pressure on supply chains today and in the future do not have historical precedence. This is one of the reasons why logistics and supply chains will continue to be important factors of differentiation in the market for a long time in the future. But what are the future tendencies for the management of supply chains and how should managers prepare themselves for these tendencies? The goal of this article is to briefly revisit the history of the field and then explore these questions.